Soil aggregation as affected by application of diverse organic materials - Maman Garba; Charles Wortmann; Humberto Blanco‐Canqui (Agrosystems, Geosciences & Environment, 2020)
Abstract Application of organic materials can amend soil for improved water infiltration and reduced erodibility with effects varying with soil properties and the organic amendment type and rate. The effects of four livestock manures, three municipal biosolids, and one industrial by‐product on dry and wet soil aggregate stability were evaluated at six sites in Nebraska. The amendments had similar C/N ratios but the biosolids had relatively high concentrations of lignin and cellulose. Soil organic matter (SOM) ranged from 21 to 65 g kg−1 and soils were silty clay loam, silt loam, or loamy sand. Soil was sampled for the 0‐ to 0.05‐m depth at physiological maturity of the second corn (Zea mays L.) crop following amendment application. Aggregation was high with no amendment applied as >95% of the soil was in water stable aggregates (WSA) > 0.053 mm and was not affected by amendments with a few exceptions such as an increase in dry aggregate size and WSA 0.25–2.0 mm at one location. Dry aggregate size was much less for the loamy sand than with other soils. With SOM >60 g kg−1 compared with less SOM, there was 42% more WSA >2 mm and 38% less WSA <2 mm diam. It cannot be concluded that organic amendment application will improve aggregation if SOM >20 g kg−1 but larger effects may have occurred with: sampling sooner after amendment application; a 0‐ to 0.025‐m sampling depth; or sampling at several months after harvest for reduced effect of the rhizosphere on aggregation.